Influence of playful texts on the production of texts by university students - Morón Hernandez, Julia Liliana (2021)
The research aimed to determine the influence of playful texts on the production of texts in the students of the III Cycle, Mention: Language and Literature of the Faculty of Education of UNSLG, the diagnosis were made that allowed to corroborate the limitations to produce texts of students and propose the use of playful texts recreationally convinced that the game is a refreshing and motivating learning resource , we raise our general and specific problem. The research was of a type applied with quasi-experimental design, experimental method, the sample: 55 students distributed in experimental group, 30 students and control group, 25 students, after applying the instruments, the results obtained verified the hypothesis: The playful texts significantly influence the production of texts in the students of the III Cycle of the mention of Language and Literature of the Faculty of Education.  In the evaluation In the entry assessment with respect to text production, the control group obtained 80% in the deficient category, 15% in the regular category and 5% in the very poor category; the experimental group in the deficient category gained 95% and 5% in the very deficient category. In the output evaluation the control group obtained 70% in the deficient category, 30% in the regular category and the experimental group obtained 75% in the regular category, 15% in the good category and 10% in the deficient category.